Sistema de recomendação de corretivos e fertilizantes para o meloeiro com base no balanço nutricional. - Deus, José Aridiano Lima de (2012)
The melon is one of cucurbitaceae most demanding in relation to fertilization, being necessary knowledge of soil, nutritional requirements and nutrient use efficiency, for a proper fertilization. The objective was parameterization of a system for recommendation of fertilizers for the melon (Ferticalc-Melon) based on the nutrient balance. The system features a module for soil acidity correction using two methods of liming. To estimate the fertilizer recommended, the system was subdivided: requirement subsystem (REQ), which includes the demand for nutrients by the plant, whereas the efficiency of nutrient recovery, and a dose that meets the criterion of "sustainability" only for the nutrient K, and supply subsystem (SUP), which corresponds to the supply of nutrients from the soil and irrigation water. After determining the REQamount and SUPamount, held the nutritional balance, in which a positive result (REQ > SUP), it is recommended that the application of fertilizer, and negative or zero (REQ ≤ SUP), not recommended to apply. Simulations were made for four different types of melon: Amarelo, Cantaloupe, Gália e Pele-de-sapo, in the range of productivity expected total of 15,000 to 45,000 kg ha-1 considering different values of P-rem. The system estimated that the Gália was the least demanding in P while Pele-de-sapo was the most demanding. Among the types, Cantaloupe was the least demanding in N and Ca, while the Amarelo requires less K, Mg and S. For the micronutrients, Amarelo was the least demanded that Fe, Cu and Zn, whereas Mn was less demanded by Cantaloupe. The supply of nutrients K, Ca and Mg by irrigation water were respectively, 23.40; 1,216.00 e 136.08 kg ha-1 to soil conditions (AS - I) and 6.24; 48.00 and 4.86 kg ha-1 to (AS-II). In general, the system recommended fertilization with macronutrients for (AS-II) except for Mg and Ca, while for (AS-I) was recommended only N and P, due to high levels of K, Ca and Mg in the soil and irrigation water. Compared with other methods the system proved to be more dynamic and flexible in its recommendations. By analyzing the sensitivity of the system, found that the variable that most influenced the recommendations was the productivity, then the nutrient content in soil. The system showed good results in relation to the recommendations, but needs to be evaluated under field conditions for your improvement in future versions.